2008
DOI: 10.1038/cmi.2008.34
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Thymus Aging Related Protein Rwdd1

Abstract: By using DDRT-PCR and EST segment ligation, a novel mouse thymus involution related gene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The same reduction is shown dealing with the proliferative cell staining with Ki67; 3-fold more is the level of apoptotic TECs in aged mice thymus (Gui et al 2007). Kang et al (2008) discovered an androgen receptor (AR) RWD domain containing 1 (Rwdd1) that is markedly decreased in aged and oxidatively stressed mice on thymocytes and TECs. AR is connected with the thymus involution.…”
Section: Murine Thymic Involutionmentioning
confidence: 59%
“…The same reduction is shown dealing with the proliferative cell staining with Ki67; 3-fold more is the level of apoptotic TECs in aged mice thymus (Gui et al 2007). Kang et al (2008) discovered an androgen receptor (AR) RWD domain containing 1 (Rwdd1) that is markedly decreased in aged and oxidatively stressed mice on thymocytes and TECs. AR is connected with the thymus involution.…”
Section: Murine Thymic Involutionmentioning
confidence: 59%
“…TGFβRII [TGF (transforming growth factor)-β type II receptor] gene expression was also not significantly different between the three groups ( Figure 5E). Rwdd1 (Rwd-domain-containing 1) is a recently characterized thymus aging-related protein that has been suggested to be indirectly involved in AR signalling [26]. The expression level of Rwdd1 in the thymus from PLP and recuperated animals was similar to controls ( Figure 5F).…”
Section: Genes Involved In Thymic Growth and Agingmentioning
confidence: 75%
“…However, due to the complexity of the aging process, the underlying mechanisms of age-related thymus involution are not well understood. To investigate the gene expression patterns in thymuses from aged mice, we performed differential display reverse (1) transcriptase polymerase chain reaction (DDRT-PCR) using total RNA from thymus of 1-month and 10-month old mice. Our previous study suggested Rwdd1 is a thymus-aging related protein (1).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the gene expression patterns in thymuses from aged mice, we performed differential display reverse (1) transcriptase polymerase chain reaction (DDRT-PCR) using total RNA from thymus of 1-month and 10-month old mice. Our previous study suggested Rwdd1 is a thymus-aging related protein (1). Currently, the detailed way of Rwdd1 functioning is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation